The Genus Eriosema (Fabaceae): From the Ethnopharmacology to an Evidence-Based Phytotherapeutic Perspective? - Ateba, Sylvin Benjamin; Njamen, Dieudonné; Krenn, Liselotte (Frontiers in Pharmacology, 2021)
The genus Eriosema (Fabaceae) includes approximately 150 species widely distributed across tropical and subtropical regions of the world (Africa, Neotropics, Asia and Australia). Throughout these regions, several species are used since centuries in different traditional medicinal systems, while others are used as food or food supplement. The present review attempts to critically summarize current information concerning the uses, phytochemistry and pharmacology of the Eriosema genus and to evaluate the therapeutic potential. The information published in English and French (up to September, 2020) on ethnopharmacology or traditional uses, chemistry, pharmacology and toxicology of Eriosema genus was collected from electronic databases (SciFinder, PubMed, Google, Google Scholar, Scopus, Web of Science, Prelude Medicinal Plants - http://www.ethnopharmacologia.org/recherche-dans-prelude/?plant, The Plant List (http://www.theplantlist.org/), POWO (http://powo.science.kew.org/) and IUCN Red List Categories (https://www.iucnredlist.org/)), conference proceedings, books, M.Sc and Ph.D dissertations. The information retrieved on the ethnomedicinal indications of Eriosema genus allowed to list 25 species (~16.6% of the genus). The majority of uses is recorded from Africa. Phytochemical analyses of 8 species led to the identification and/or isolation of 107 compounds, with flavonoids (69.2%), chromones (7.5%) and benzoic acid derivatives (3.7%) as the main chemical classes. Pharmacological investigations with crude extracts and isolated compounds showed a broad range of activities including aphrodisiac, estrogenic, anti-osteoporosis, hypolipidemic, anti-diabetic, anti-diarrheal, anti-microbial, anti-oxidant, anthelmintic, anti-cancer, and acetylcholinesterase inhibitory activities. Despite the low number of Eriosema species tested, there is convincing evidence in in vitro and in vivo studies validating some traditional and ethnobotanical uses. However, the utility of several of the described uses has not yet been confirmed in pharmacological studies. Reviewed data could serve as a reference tool and preliminary information for advanced research on Eriosema species.